Oposisi Biner Dalam Mitologi Mesir Kuno: Sebuah Analisis Hitoriografi Feminis - Fikri Labib Fajar; Amalia Sri Sulanjari (CV. AFDIFAL MAJU BERKAH, 2026)
This study explores how gender is represented in Ancient Egyptian mythology through the concept of binary opposition and a feminist historiographical perspective. It employs a qualitative research design using textual and historiographical approaches. The primary data consist of selected Ancient Egyptian mythological narratives involving gods and goddesses. These texts are analyzed interpretatively through Claude Lévi-Strauss’s theory of binary opposition and Joan Wallach Scott’s feminist historiographical framework. Within Ancient Egyptian civilization, mythology functioned not only as a religious system but also as a symbolic space in which social values and structures were expressed. The analysis identifies recurring oppositional patterns between masculine and feminine divine figures. Masculine figures tend to be associated with authority, control, and power, whereas feminine figures are more often connected with nurturing, protection, and relational roles. These distinctions indicate a hierarchical pattern in which masculine attributes are positioned as more dominant. From Scott’s perspective, such representations can be understood as part of a broader construction of gender that reflects patriarchal tendencies within mythological narratives. Although some variations and ambiguities are present, the dominant pattern places male figures in more authoritative positions, while female figures are frequently defined in relation to them. Therefore, the study challenges the assumption that women in Ancient Egyptian society experienced full equality, particularly when examined through symbolic and narrative structures.